2013
DOI: 10.1590/s1981-57942013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Interface sintaxe-fonologia: desambiguação pela estrutura prosódica no português brasileiro

Abstract: O objetivo deste artigo é a análise das estratégias prosódicas de desambiguação de sentenças em português brasileiro (PB), em contexto de ambiguidade sintática e choque acentual.² Nossa hipótese é a de que a desambiguação dessas sentenças se dê através de diferentes estratégias prosódicas de desfazimento do choque acentual. Para testar essa hipótese, foram realizados experimentos de produção e de percepção com falantes do PB. Os resultados obtidos foram analisados à luz da Fonologia Prosódica (NESPOR; VOGEL, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
5
0
3
Order By: Relevance
“…Future studies could model secondary stress and reduced vowels of Brazilian Portuguese, both as a means of increasing accuracy in detection, and as a means of investigating secondary stress, and its interactions with primary stress in continuous speech. The question of stress alternation needs further examination: results indicate that, even though stress shift in the context herein investigated may not be categorical, some speakers appear to do it in the phonological context described in [11]. Importantly, future studies should use data from typologically different languages, as it would be interesting to learn if comparable results are found.…”
Section: Conclusion and Future Researchmentioning
confidence: 85%
See 1 more Smart Citation
“…Future studies could model secondary stress and reduced vowels of Brazilian Portuguese, both as a means of increasing accuracy in detection, and as a means of investigating secondary stress, and its interactions with primary stress in continuous speech. The question of stress alternation needs further examination: results indicate that, even though stress shift in the context herein investigated may not be categorical, some speakers appear to do it in the phonological context described in [11]. Importantly, future studies should use data from typologically different languages, as it would be interesting to learn if comparable results are found.…”
Section: Conclusion and Future Researchmentioning
confidence: 85%
“…The second experiment in this study examined (potential) stress alternations in Brazilian Portuguese: in [11], it is reported that, in cases of structural ambiguity where the words involved are in a context of stress clash, if such clash is resolved by means of stress shift, the cue is that a single phonological phrase (PhP) is formed, and the interpretation will be that the second word involved in the clash modifies the word that immediately precedes it. If, however, clash is resolved by the insertion of pauses and/or the addition of a tone accent to each of the words involved, two distinct phonological phrases are formed, and the interpretation will be that the second word involved in the clash modifies a word other than the one that immediately precedes it.…”
Section: Stress Shift In Continuous Speech?mentioning
confidence: 99%
“…For instance, given that optional stress shift only takes place within PhPs in BP, it always prompts the reading in (10a) below. By contrast, the insertion of a pause or the association of a pitch accent with each word involved in the clash prompts the reading given in (10b), as these are processes that apply between PhPs (Gravina & Fernandes-Svartman, 2013; example taken from Guimarães, 1998). 10 Tonal marking also makes reference to PhP in both varieties, although in different ways.…”
Section: Clitic-host Combinations and Compound-like Groupingsmentioning
confidence: 99%
“…(O caFÉ)ϕ (LUta)ϕ pelo prémio do produto mais qualificado 'The coffee disputes the award for the best product' In BP, different prosodic domains also show different means to resolve internal stress clashes. Within the PhP, (optional) stress shift is applied, as in (9a) vs. (9b) (Abousalah 1997).When the stress clash occurs between PhPs, as in (9b), one clash-avoiding strategy consists in inserting a pause between the clashing syllables(Gravina & Fernandes-Svartman 2013).7 The fact that stress shift is the preferred option not only in sentences such as (9a), but also in (9c), where the adjective follows the nominal head, provides evidence for the possibility of reestructuring non-branching phonological phrases with the preceding PhP in this variety.…”
mentioning
confidence: 99%
“…Assim, o uso das outras estratégias não impede o caso da segunda palavra ser adjunta da primeira. De qualquer maneira, em sentenças ambíguas, o falante parece guardar as estratégias de pausa e evento tonal para quando não há relação entre a primeira e a segunda palavras (GRAVINA & SVARTMAN, 2013 […”
Section: Figura 3: Carro Quebrado -Adjunçãounclassified